THE EQUITY FACTORS THAT INFLUENCE BEHAVIORAL LOYALTY OF GRABFOOD APPLICATION USERS: STUDY OF GEN Z CONSUMERS IN DKI JAKARTA - Gotama, Nathan Indra; Ekawati , Sanny (International Journal of Application on Economics and Business, 2025)
This study examines the impact of equity factors on behavioral loyalty through attitudinal loyalty among Gen Z consumers of the GrabFood application in DKI Jakarta. Quantitative method was applied in this study through a google form questionnaire with Likert scale. Data was collected from 145 Gen Z consumers who used the GrabFood application at least once in the last 2 months. This study employs a purposive sample strategy in conjunction with the aid of SmartPLS 4.0 software. According to the findings of the Structural Equation Modeling (SEM), attitudinal loyalty is significantly positively impacted by the third component of customer-perceived equity. Moreover, connection equity significantly improves behavioral loyalty, although brand equity and value equity have little influence on the same. Behavioral loyalty is significantly positively impacted by the attitudinal loyalty component as well. The association between brand equity and value equity and behavioral loyalty can be mediated by attitudinal loyalty characteristics, according to mediation tests. However, the relationship between behavioral loyalty and relationship equity cannot be mediated by attitudinal loyalty. The study reveals that it is important for business owners to add value to their brands and build positive relationships with brand customers, as attitudinal loyalty to a brand is determined by value equity, brand equity, and relationship equity. On the other hand, customer behavioral loyalty is often determined by the attitudinal loyalty of the customers which further explains why businesses should increase a positive attitude towards the brand.